Structural modifications of the antimicrobial peptide ubiquicidin for pulmonary imaging of bacteria in the alveolar space. (25th February 2016) - Akram, Ahsan R; Avlonitis, Nicolaos; Craven, Thomas; Vendrell, Marc; McDonald, Neil; Scholefield, Emma; Fisher, Andrew; Corris, Paul; Haslett, Christopher; Bradley, Mark; Dhaliwal, Kevin
Abstract: Background: The direct visualisation of bacteria in the distal lung would increase the spatiotemporal understanding of pulmonary infection and be a powerful tool to stratify patients with suspected pneumonia. In critically ill patients, the diagnostic dilemma of pulmonary opacities leads to overprescribing of antimicrobial agents while waiting for culture results from bronchoalveolar lavage. Ubiquicidin (UBI) is an innate cytosolic antimicrobial peptide with a twelve aminoacid portion (UBI29–41 ) that specifically binds bacteria. We aimed to modify the chemical structure of UBI29–41 so that in-situ bacterial imaging with optical endomicroscopy (OEM) could be achieved. Methods: UBI29-41 compounds were labelled with the environmentally sensitive fluorophore NBD (NBD-UBI), with incorporation of synthetic aminoacids (NBD-UBInma ) and alteration of the secondary structure of the native peptide on a dendrimeric scaffold (NBD-UBIdend ). These compounds were assessed in vitro and delivered endobronchially in an ex-vivo sheep lung model and then OEM applied to allow alveolar imaging. The NBD-UBIdend –OEM platform was also evaluated in explanted whole cystic fibrosis lungs. Findings: NBD-UBI selectively labelled bacteria over mammalian cells but remained susceptible to proteolytic degradation and poor affinity. NBD-UBInma improved stability but not affinity. NBD-UBIdend remained structurally stable and exhibited high affinity for bacteria in vitro. It retained bacterial selectivity over mononuclear cells (p=0·0015), neutrophils (p=0·0034), bronchoalveolar lavage macrophages (p=0·0169), and labelled Escherichia coli (p=0·0035), Klebsiella pneumoniae (p=0·0003), Pseudomonas aeruginosa (p=0·0009), and meticillin-sensitive Staphylococcus aureus (p<0·0001) segments in situ in an ex-vivo sheep lung model (area under the curve 0·926, SE 0·056; p=0·000128) with a relevant limit of detection of 1 × 10 5 colony-forming units per mL on lavage. NBD-UBIdend also detected bacteria in situ in ex-vivo explanted human cystic fibrosis lungs (p=0·0027 compared with peptide and fluorophore control segments). Interpretation: We describe an OEM strategy that can immediately detect bacteria in size-relevant preclinical models, with crucial requirements for pulmonary molecular imaging of peptide stability and affinity. This method has the potential to stratify pulmonary opacities in the intensive care unit when pneumonia is suspected and offers the substantial advantage of real-time detection, therefore allowing immediate decision making about antimicrobial treatment. This imaging strategy is now undergoing first-in-man translation. Funding: Wellcome Trust, Department of Health, Engineering and Physical Sciences Research Council.